Brachytherapy for uterine cervix-limited acute myeloid leukemia relapse - Beziat, Guillaume; Tavitian, Suzanne; Arnaud, Francois-Xavier; Izar, Françoise; Attal, Justine; Borel, Cécile; Recher, Christian; Ducassou, Anne (Journal of Contemporary Brachytherapy, 2022)
Acute myeloid leukemia (AML) may extend to extra-medullary sites at diagnosis or at relapse, either isolated or associated with bone marrow disease. Granulocytic sarcoma of uterine cervix is rare, and there is no established treatment for this disease. Two cases of uterine cervix-limited AML relapse showed that brachytherapy may be an effective therapeutic option in this setting along with chemotherapy, with good tolerance.